Experimental assessment of robust reference genes for qRT-PCR in lung cancer studies - Gu, Wei; Wang, Yubin; Xu, Ran; Li, Jiamin; Jin, Jingjie; Zhao, Jing; Chen, Yang; Lu, Yuanzhi; Zhang, Gong (Frontiers in Oncology, 2023)
Stable internal reference genes are crucial for quantitative real-time PCR (qRT-PCR) analysis in lung cancer studies. The widely-used reference genes are mostly chosen by intuition or from pan-cancer transcriptome data, lacking experimental validation in qRT-PCR in the context of lung cancer. This study evaluated the stability of the candidate reference genes in lung cancer cell lines under normal homeostasis, hypoxia, and serum deprivation conditions, to screen the robust reference genes for qRT-PCR in lung cancer studies. The stability of reference gene combinations was also assessed. We found that most stably expressed genes from pan-cancer transcriptome analyses are not stable enough under some tested conditions. CIAO1, CNOT4 and SNW1 are the most stable reference genes under various conditions. The stability is further increased by combining more reference genes. We experimentally demonstrated using the hypoxia biomarker HIF-2α that choosing inappropriate reference gene would lead to wrong qRT-PCR conclusion. We also found that the stable reference genes are irrelevant to the malignancy, which may explain their stability in various conditions, in which the cancer cells often encounter. This study provided a list of validated stable qRT-PCR reference genes and reference gene combinations for lung cancer, which may standardize qRT-PCR experiments in future lung cancer studies.